Undifferentiated sarcoma of the liver - Lizaso, Isabel; Chavarría, Oscar; Berazategui, Ruver; Gutiérrez, Carmen; Ventos, Pedro (Cirugía del Uruguay, 1991)
The author presents a case of undifferentiated hepatic sarcoma (UHS) in a 13 year old child treated with right hepatectomy and postoperative chemotherapy, with a 2 year fre